2019
DOI: 10.1111/dom.13667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cilostazol, a phosphodiesterase‐3 inhibitor, on coronary artery stenosis and plaque characteristics in patients with type 2 diabetes: ESCAPE study

Abstract: Aim: To perform a prospective study to evaluate the effect of cilostazol (CTZ) compared with aspirin (acetylsalicylic acid; ASA) in Korean people with diabetes and subclinical coronary atherosclerosis.Materials and methods: A total of 100 people with diabetes who had mild to moderate coronary atherosclerosis, assessed by coronary computed tomographic angiography (CCTA), were randomly assigned to either 200 mg/d CTZ or 100 mg/d ASA (n = 50 each group). The primary outcome was change in coronary artery stenosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 54 publications
2
39
0
Order By: Relevance
“…In the present study, a significant increase in serum HDL cholesterol and a significant decrease in triglyceride levels were observed only in the CTZ group, which was in accordance with the findings of previous studies 23,24,40 . Cilostazol therapy increases lipoprotein lipase activity, which plays a crucial role in lipid metabolism in adipose tissue 22 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, a significant increase in serum HDL cholesterol and a significant decrease in triglyceride levels were observed only in the CTZ group, which was in accordance with the findings of previous studies 23,24,40 . Cilostazol therapy increases lipoprotein lipase activity, which plays a crucial role in lipid metabolism in adipose tissue 22 .…”
Section: Discussionsupporting
confidence: 93%
“…However, those researchers found that cilostazol therapy increased the fibrous components and decreased the lipid/necrotic components in the carotid plaque. Moreover, we previously published a clinical study in which treatment with cilostazol for 1 year decreased the plaque volume of coronary arteries in patients with T2D (the ESCAPE study) 40 . There were several differences between the ESCAPE and the present study, including the study duration and period and the percentage of patients with comorbidities, such as hypertension and dyslipidaemia.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Cilostazol is a phosphodiesterase inhibitor with antiplatelet activity. 8 A previous study demonstrated that the continued use of cilostazol for 12 weeks could lower uric acid levels in patients with impaired glucose tolerance or type 2 diabetes. 9 In addition, cilostazol effectively reduced P2Y12 reaction units in clopidogrel-resistant patients and increased platelet inhibition.…”
Section: Discussionmentioning
confidence: 99%